2018
DOI: 10.5505/tjtes.2018.62753
|View full text |Cite
|
Sign up to set email alerts
|

The significance of hemogram on diagnosis of acute appendicitis during pregnancy

Abstract: BACKGROUND: Acute appendicitis (AA) is the most common emergency surgical condition during pregnancy after obstetric and gynecological pathologies. Urgent and accurate diagnosis of AA in pregnant patients reduces maternal and fetal morbidity/mortality rates. This study evaluated the significance of hemogram to diagnose AA during pregnancy.METHODS: Forty-seven pregnant patients operated for AA in the Ordu or Ondokuz Mayis University Medical School Hospitals between January 2007 and December 2017 were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
3
22
1
1
Order By: Relevance
“…However, a number of studies have indicated that there might be an increased risk of preterm delivery or fetal loss in those undergoing laparoscopic appendicectomy compared with those undergoing open appendicectomy (24,25). Whether the choice of incision should be transverse or oblique or at or above McBurney's point in pregnant women is also a controversial issue (18,26). Our study showed that oblique incisions at McBurney's point could be performed successfully in all pregnant patients.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, a number of studies have indicated that there might be an increased risk of preterm delivery or fetal loss in those undergoing laparoscopic appendicectomy compared with those undergoing open appendicectomy (24,25). Whether the choice of incision should be transverse or oblique or at or above McBurney's point in pregnant women is also a controversial issue (18,26). Our study showed that oblique incisions at McBurney's point could be performed successfully in all pregnant patients.…”
Section: Discussionmentioning
confidence: 63%
“…As reported in another study, the contributions of inflammation markers alone are limited, and thus their use must only be to contribute to diagnosis together with physical examination and imaging tests (18).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Twenty-four articles were retrieved and reviewed based on full text. Finally, 11 articles met the inclusion criteria and were included in our meta-analysis [26][27][28][39][40][41][42][43][44][45][46].…”
Section: Literature Searchmentioning
confidence: 99%
“…Ten of the 11 studies reported adult patients while one included pediatric patients [28]. Five studies extracted effect estimates using indirect methods proposed by Wan et al [26,27,40,41,45]. Most of the included studies were conducted in Europe and Asia.…”
Section: Study Characteristicsmentioning
confidence: 99%